Optimal Time for Pharmacological Treatment of Abdominal Aortic Aneurysm - Iida, Yasunori; Sawa, Shigeharu; Shimizu, Hideyuki (Current Drug Targets, 2018)
Background: Abdominal aortic aneurysm (AAA), if left untreated, poses the main risks of progressive expansion, rupture, and hemorrhage, leading to death. Large AAA with a risk of rupture is usually treated by graft replacement or endovascular aneurysm repair. Nonsurgical treatment is not an alternative for large AAA, but is potentially beneficial for small AAA which usually requires a watchful waiting approach with medication. Objective: We introduce current clinical research regarding the pharmacological treatment of small AAA and assess the optimal time for starting the treatment. Results: Data from current clinical researches on pharmacological treatment of AAA investigating the efficacy of pharmacological treatment to limit AAA growth were presented and introduced the medicines currently evaluated by randomized controlled trials for their efficacy for AAA. Conclusion: The optimal time to administer pharmacological treatment for AAA is during the stage wherein its diameter is still small. To detect early small-diameter AAA, screening tests are mandatory in high-risk patients. For pharmacological treatment, the drug that shows acceptable results in clinical tests and is the most effective for the patient's condition should be carefully selected. Lifestyle changes should also accompany pharmacological treatment.
Keywords: endovascular aneurysm repair